Cerebrospinal fluid biomarkers in psychiatric autoimmune encephalitis: a retrospective cohort study - Hansen, Niels; Juhl, Aaron Levin; Grenzer, Insa Maria; Teegen, Bianca; Wiltfang, Jens; Fitzner, Dirk (Frontiers in Psychiatry, 2023)
Background: Psychiatric autoimmune encephalitis (pAE) is a growing field of interest in diagnosis and therapy in psychiatric hospitals and institutions. This study investigates the relevant extent to which there are potential biomarkers in cerebrospinal fluid (CSF) that can differentiate against a cohort with neurodegenerative disease. Methods: We included in this study a total of 27 patients with possible and definite psychiatric autoimmune encephalitis and compared with a cohort with CSF-based AD (n=27) different biomarkers in CSF such as lactate, cell count, % lymphocytes, % monocytes, total protein content, albumin, immunoglobulins G (IgG), M (IgM) and A (IgA), CSF/serum albumin ratio, CSF/serum IgG ratio, CSF/serum IgA ratio, intrathecal IgG synthesis, blood-brain barrier disruption, specific antibody synthesis for measles, rubella, herpes simplex virus, varicellan zoster virus, Ebstein-Barr virus and cytomegalovirus, total tau protein (t-tau), phosphorylated tau protein 181 (p-tau181), amyloid beta 42 (Aß42), amyloid beta 40 (Aß40) and the amyloid beta 42/ amyloid beta 40 (Aß42/40) ratio. Results: The p-tau 181 was elevated above cut-off values in both possible pAE and AD. However, in definitive pAE, p-tau181 levels were not elevated. When elevated p-tau181 levels in possible AE were compared with those in AD, we found relevant differences, such as a relative increase in p-tau181 in AD patients. Elevated p-tau181 levels were detected in possible psychiatric AEs with IgLON5, glycine, recoverin, titin, and nonspecific neuropil antibodies in serum and IgLON5, titin, Yo, and nonspecific neuropil autoantibodies in CSF. In addition, we detected elevated levels of p-tau181 and IgLON5 autoantibodies in serum and CSF, and Yo autoantibodies in CSF in patients with definitive pAE. Interestingly, we observed a higher CSF/serum IgM ratio in possible and definitive pAE than in AD patients. Conclusions: Our results suggest that neuroaxonal brain damage may occur in specific psychiatric AEs associated with IgLON5, glycine, recoverin, and titin autoantibodies. Further research should focus on the CSF/serum IgM ratio as an early marker of autoantibody production in pAE compared to AD as a potential biomarker for differential diagnosis.